The Incentive Effects of Property Taxation: Evidence from Norwegian School Districts - Jon H. Fiva; Marte Rønning (Statistics Norway, Research Department, 2006)
Recent theoretical contributions indicate favorable incentive effects of property taxation on public service providers. The object of this paper is to confront these theories with data from Norwegian school districts. The institutional setting in Norway is well suited for analyzing the effects of property taxation because one can compare school districts with and without property taxation. To take into account potential endogeneity of the choice of implementing property taxation, we rely on instrumental variable techniques. The empirical results indicate that, conditional on resource use, property taxation improves school quality measured as students' result on the national examination.
Keywords: C21; H71; I22; 330; Property taxation; Disciplining device; Public sector quality